Alternatives to Low Molecular Weight Heparin for Anticoagulation in Pregnant Women with Mechanical Heart Valves in Middle-Income Countries: A Cohort Study. Issue 1 (13th October 2021) - Keepanasseril, Anish; Pillai, Ajith Ananthakrishna; Baghel, Jyoti; Pande, Swaraj Nandini; Mondal, Nivedita; Munuswamy, Hemachandren; Kundra, Pankaj; D'Souza, Rohan
Objective: To compare cardiac complications and pregnancy outcomes in women with mechanical heart valves (MHVs) on two different anticoagulation regimens in a middle-income country. Methods: We conducted a retrospective cohort study comparing outcomes in pregnant women with MHVs that received vitamin K antagonists (VKAs) throughout pregnancy versus sequential anticoagulation (heparins in the first trimester and peripartum period and VKAs for the remainder of pregnancy), at a tertiary centre in South India, from January 2011 to August 2020. Results: We identified 138 pregnancies in 121 women, of whom 32 received VKAs while 106 were on sequential anticoagulation. There were no differences between groups with regard to maternal deaths [0 vs. 6 (5.7%), p = 0.34], thromboembolic events [2 (6.3%) vs. 15 (14.2%), p = 0.36], haemorrhagic complications [4 (12.5%) vs. 12 (11.3%), p = 0.85], cardiac events [1 (3.1% vs. 17 (16%), p = 0.07], spontaneous miscarriages [5 (15.6%) vs. 13 (12.3%), p = 0.62], stillbirths [0 vs. 5 (5.4%), p = 0.581] or neonatal deaths [2 (8.7%) vs. 1 (1.1%), p = 0.11]. Both cases of warfarin embryopathy received >5 mg warfarin in the first trimester. Thromboembolic events were associated with subtherapeutic doses of heparin in the first and third trimesters and the early postpartum period. Fetal growth restriction and preterm birth complicated 34 (29.3%) and 26 (22.4%) pregnancies respectively. Conclusion: Pregnancy complications associated with MHVs in middle-income countries may be reduced by multidisciplinary surveillance, avoiding first-trimester warfarin if daily doses >5 mg and ensuring therapeutic levels of heparin during bridging in the first and third trimesters and peripartum period. Administration of low-dose aspirin should be considered as this may prevent placentally-mediated complications of pregnancy. Highlights: Pregnancy complications associated with MHVs in LMICs may be reduced by multidisciplinary surveillance, avoiding first-trimester warfarin if the daily dose is >5 mg, ensuring therapeutic levels of heparin in the first trimester and peripartum period. Placentally-mediated complications of pregnancy can be prevented by administering low-dose aspirin. Vitamin K antagonists or sequential regimen can be used as suitable alternatives to LMWH for anticoagulation in pregnant women with MHVs.